Two new species and a new record of Scale-worms (Polychaeta) from Southwest Atlantic deep-sea coral mounds - Miranda, Vinícius Da Rocha; Brasil, Ana Claudia Dos Santos (Zootaxa, 2014)
Two new species of scale-worms, Harmothoe ruthae sp. nov. (Polynoidae) and Pholoides sinepapillatus sp. nov. (Sigalionidae) are described. In addition, we expand the description of Harmothoe gilchristi and extend its distribution to the Southwest Atlantic. The three species were found among the species of corals Lophelia pertusa, Solenosmilia variabilis, Enallopsammia rostrata, Madrepora oculata and Errina sp., a total of 257 samples of these corals were taken between 570 m and 1040 m depth, at the North-East coast of Rio de Janeiro, Brazil.